DIGITAL SOLUTION FOR LONELINESS AND SOCIAL ISOLATION IN THE MIDDLE AGE - Bachate, Ravindra; Harchekar, Ruta; Sawant, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
ocial isolation and loneliness are critical concerns affecting middle-aged adults (45-64), impacting their mental and physical well-being. This research delves into the intricate factors contributing to this issue, including changing family dynamics, workplace challenges, and the complex influence of technology. This study adopts a qualitative approach, drawing on in-depth interviews with middle-aged individuals to understand their experiences, needs, and challenges related to loneliness. The research identifies multifaceted causes, including "empty nest" syndrome, career shifts, and evolving social circles. It highlights the negative effects of loneliness on mental and physical health, while acknowledging the limited understanding of the interplay between diverse factors and the unexplored potential of digital solutions for this specific demographic. The study reveals gaps in understanding integrated strategies that consider psychological, social, cultural, and environmental influences. It emphasizes the need for research focusing on the unique dynamics of midlife and the nuanced impact of technology on their social well-being and underscores the value of qualitative research in capturing individual experiences often masked by quantitative data. By addressing these gaps and promoting empathetic, connection-driven interventions, we can foster meaningful social engagement and combat loneliness in middle-aged adults. The research proposes a multifaceted approach, including age-appropriate activities, awareness campaigns, and culturally sensitive support programs. It further highlights the potential of technology-driven solutions, advocating for responsible development and mindful integration to bridge the social gap. This study highlights the need for inclusive and comprehensive remedies while deepening our understanding of social isolation and loneliness in midlife. Improved research on the effects of technology and the creation of customized solutions could benefit middle-aged people's social connections and general well-being.